2023
DOI: 10.1021/acsanm.3c03008
|View full text |Cite
|
Sign up to set email alerts
|

SnO2-Coated Silver Nanowire Networks as a Physical Model Describing Their Reversible Domain under Electrical Stress for Stable Transparent Electrode Applications

Laetitia Bardet,
Masoud Akbari,
Chiara Crivello
et al.

Abstract: Thermal, electrical, and chemical instabilities affect the efficient integration of silver nanowire (AgNW) networks as transparent electrodes for energy and wearable electronics. By coupling experimental data and a simple physical model, we deduce the electrical areal power density ranges that AgNW networks can withstand, to observe either reversible modifications (i.e., electron− phonon interaction) or irreversible modifications (i.e., electrical sintering or degradation). This approach also allows us to pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…To address this issue, significant attention has been devoted to the effects of coatings, aimed at enhancing the AgNW stability under thermal stress. 12 For instance, we have previously demonstrated that even thin SnO 2 coatings 15,17 deposited by Atmospheric Pressure Spatial Atomic Layer Deposition (AP-SALD) can significantly enhance the thermal stability of AgNW networks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address this issue, significant attention has been devoted to the effects of coatings, aimed at enhancing the AgNW stability under thermal stress. 12 For instance, we have previously demonstrated that even thin SnO 2 coatings 15,17 deposited by Atmospheric Pressure Spatial Atomic Layer Deposition (AP-SALD) can significantly enhance the thermal stability of AgNW networks.…”
Section: Resultsmentioning
confidence: 99%
“…42 The AP-SALD growth of SnO 2 thin films was carried out using tin( ii ) acetylacetonate (Sn(acac) 2 ) and water as precursors. 17,43 The samples were positioned 150 μm away from the injection head. During the deposition process, the growth rate of SnO 2 deposition performed at 200 °C was approximately 1.2 nm min −1 .…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The utilized AP-SALD employed a proximity method relying on a gas manifold. A detailed explanation of the experimental procedure and deposition parameters used can be found in refs ,, . The distance between the substrate and the AP-SALD head was set to 150 μm.…”
Section: Methodsmentioning
confidence: 99%
“…An alternative low-cost and fast coating method is atmospheric-pressure spatial atomic layer deposition (AP-SALD). Several reports have shown that this technique is capable of producing high-quality conformal films on the AgNWs, such as ZnO, , Al:ZnO, and SnO 2 . , The coatings improved the stability of AgNWs, since the metal oxide layer hinders the surface diffusion of the Ag atoms from nanowires, thus maintaining the integrity and stability of the nanowire morphology. For most oxides, the stability of AgNWs improves as the coating thickness increases.…”
Section: Introductionmentioning
confidence: 99%